2022
DOI: 10.1155/2022/6328807
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Low-Dose Aspirin Combined with Vitamin E on the Incidence of Intrauterine Growth Restriction and Hemorheological Indexes of Pregnant Women in Patients with Gestational Hypertension

Abstract: Objective. To investigate the effect of low-dose aspirin combined with vitamin E on the incidence of intrauterine growth restriction and hemorheological indexes of pregnant women in patients with gestational hypertension. Method. 134 elderly patients with chronic urticaria treated in our hospital from November 2017 to November 2020 were studied. According to the treatment methods, they were randomly divided into observation and control groups. There were 67 patients in the observation group, aged 20-37 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…[ 9 , 10 , 25 , 26 ] Several studies have even found that the prophylactic effect of aspirin has a protective effect on PPH. [ 27 , 28 ] The secondary analysis of the APPEC study demonstrated that in pregnant women with high-risk factors for developing pre-eclampsia, the prophylactic administration of low-dose aspirin from 12 weeks to 20 weeks of gestation until 34 weeks of gestation or in the event of early delivery would not increase the incidence of PPH or decrease the incidence of PPH. There was no evidence of heterogeneity in the incidence of PPH in subgroups defined according to maternal characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 , 10 , 25 , 26 ] Several studies have even found that the prophylactic effect of aspirin has a protective effect on PPH. [ 27 , 28 ] The secondary analysis of the APPEC study demonstrated that in pregnant women with high-risk factors for developing pre-eclampsia, the prophylactic administration of low-dose aspirin from 12 weeks to 20 weeks of gestation until 34 weeks of gestation or in the event of early delivery would not increase the incidence of PPH or decrease the incidence of PPH. There was no evidence of heterogeneity in the incidence of PPH in subgroups defined according to maternal characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Some research aimed to evaluate the relationship between the incidence of PPH and the prophylactic administration of low-dose aspirin showed that aspirin will not increase the risk of PPH and other bleeding events, [17–24] but some studies indicated that there was an increased risk of PPH [9,10,25,26] . Several studies have even found that the prophylactic effect of aspirin has a protective effect on PPH [27,28] . The secondary analysis of the APPEC study demonstrated that in pregnant women with high-risk factors for developing pre-eclampsia, the prophylactic administration of low-dose aspirin from 12 weeks to 20 weeks of gestation until 34 weeks of gestation or in the event of early delivery would not increase the incidence of PPH or decrease the incidence of PPH.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%